Rehabilitation of a hemimaxillectomy patient having microstomia with two-piece hollow obturator - Faisal Khan; Sunil Kumar Mishra (Wolters Kluwer Medknow Publications, 2017)
Eradication of head and neck carcinoma with surgical resection usually leave behind the patient with a large tissue defect and to rehabilitate such patients to optimum function and esthetics is a challenging task for the maxillofacial prosthodontist. The patients undergoing partial or total maxillary resections have difficulty in mastication, swallowing, speech, and social interaction. This article presents a case report of a hemimaxillectomy patient treated with a two-piece hollow acrylic bulb obturator. This case report presents a modified impression technique with a specially designed sectional tray as the patient had reduced mouth opening. The prosthesis improves the hypernasality, mastication, and speech of the patient.